The war in the Central Sierra and the controlled independence in Lima - Montoya Rivas, Gustavo (2021)
This article addresses the ideological, political, and military circumstances at the start of the war for independence in the Central Sierra, with emphasis on the participation of social actors in rural areas. Conversely, it presents the political process in Lima during the Protectorate, and the challenges it had to face before its fall on September of 1822. It also intends to establish the different nuances of the war as it unfold in both places.